Clinical Characteristics and Prognostic Factors of Testicular Sarcoma: A Population-Based Study - Wang, Xingyuan; Chen, Zeyu; Qiu, Shi; Cao, Dehong; Jin, Kun; Li, Jin; Chen, Bo; Lei, Haoran; Huang, Yin; Bao, Yige; Yang, Lu; Liu, Liangren; et al. (Frontiers in Oncology, 2021)
Objectives: To study clinical characteristics and factors that may effect the prognosis of testicular sarcoma patients. Patients and methods: In the Surveillance Epidemiology and End Results database (2006‐2016), people with testicular sarcoma were enrolled in our research. Multivariable Cox proportional hazard model and Multivariable Logistic regression model were used to compare the impact of different factors on cancer-specific survival, localized metastasis and distant metastasis. Results: This research was based on the registry information of 158 testicular sarcoma patients. All patients with a median age of 17.00 (1.00-93.00) years were pathologically diagnosed with orchiectomy or needle biopsy specimens. Patients with Grade Ⅰ, Ⅱ, Ⅲ and Ⅳ testicular sarcoma accounted for 34.29% (n =24), 10.10% (n =7), 22.86% (n = 16) and 32.86% (n = 23) of all patients, respectively. There were 42 (30.43%), 53 (38.41%), 15 (10.87%), 20 (14.49%), 5 (3.62%), 3 (2.17%) patients with Tis, T1, T2, T3, T4 and >T4 (the invasion degree exceeded the staging system of testicular cancer) disease respectively. Among all included patients, localized metastasis occurred in 31 (20.13%) patients, distant metastasis was found in 28 (18.18%) patients during observation and 61.69% (n =95) had no metastasis. 32 (20.25%) patients died of this cancer. According to our study, patients with distant metastasis [OR=17.86, 95%CI (4.63-68.84), p<0.0001] and T3 disease [OR=4.13, 95%CI (1.10-15.53), p=0.0359] were more likely to die of this cancer. Patients with advanced T stage were more likely to occur distant metastasis, [OR=13.91, 95%CI (1.80-107.54), p=0.0116] for T3 and [OR=16.36, 95%CI (1.36-196.21), p=0.0275] for T4. Conclusions: According to our research, factors including metastasis and higher T stage were significantly related with poorer prognosis of testicular sarcoma. Higher T stage was also found to be a risk factor of distant metastasis. The recognization of these poor prognostic factors may allow physicians to make comprehensive and appropriate management decision for testicular sarcoma patients.